Sovereignty Games
XIII, 252 p. 1 illus.
Keywords: This book offers an in-depth examination of the strategic use of State sovereignty in contemporary European and international affairs and the consequences of this for authority relations in Europe and beyond. It suggests a new approach to the study of State sovereignty, proposing to understand the use of sovereignty as games where States are becoming more instrumental in their claims to sovereignty and skilled in adapting it to the challenges that they face.